PENERAPAN METODE MIND MAPPING DALAM PEMBELAJARAN IPS KELAS V DI SEKOLAH DASAR (Penelitian Tindakan Kelas Pada Kelas V Tema 7; Peristiwa dalam Kehidupan di SDN Pucung III Kecamatan Kotabaru Kabupaten Karawang Tahun Ajaran 2019/2020) - Firmanda Ibrahim, Baim (2020)
This Research aims to improve the ability to understand student concept IN IPS material in Theme 7 Sub Theme 1: National event of the colonial period is still low. This research aims to improve the understanding of IPS concept through the application of mind mapping methods. The Mind Mapping method is an effective method used to develop ideas through a series of maps. This type of research is class action research (PTK) using a spiral model of Kemmis and Taggart. The stages of each cycle include planning, execution, observation, and reflection. The subject of this study is a grade V student AT SD Negeri Pucung III which amounted to 37 students. The data collection methods used are observations, tests, and documentation. The research Data is analyzed in a qualitative and quantitative descriptive. The results showed that learning with the application of mind mapping methods can improve the understanding of the CONCEPT of IPS in the class V elementary School of Pucung III. Based on the results of the tests obtained at each end of the cycle showed increased ability of understanding the concept of IPS Theme 7 sub theme 1. In cycle I occurred an increase of 21.19% ie from 63.89%, so it becomes 85.08%. A total of 35 students have reached the value of the KKM, while 2 students have not reached the value of KKM. Percentage of the average value obtained by the students that completed in Cycle II is 94.59%.